Understanding the effect of 1-D dipping anisotropic conductivity on the response and interpretation of magnetotelluric data. Issue 3 (2nd May 2022) - Darrh, Andréa; Li, Yaoguo
SUMMARY: Anisotropy in geological settings has been shown to be able to have a significant effect on data and to result in different interpretations when anisotropy is not taken into account. Recent work in inversion of electromagnetic data has emphasized the need for greater accuracy in interpretations where anisotropic effects dominate in data. We focus on how effectively inversions can extract anisotropic characteristics from magnetotelluric (MT) data for the 1-D dipping anisotropy case. We assess the sensitivity of 1-D MT data to each electrical conductivity component by examining the variability of polar plot eccentricity between analytic cases and by examining how sensitivity varies with increasing anisotropic dip angle. We apply a Tikhonov regularized inversion to both synthetic and experimental data using both an L 2 norm and an Ekblom norm to approximate an L 1 norm to identify the extent to which all model parameters associated with the 1-D dipping anisotropy case are recovered. We find that the application of an L 1 norm aids in recovering the true depth extent and horizontal conductivities of an anisotropic layer when compared to the results from a standard L 2 norm.